Unmet Needs in Pharmacological Treatment of Apathy in Alzheimer’s Disease: A Systematic Review - Theleritis, Christos G.; Siarkos, Kostas T.; Politis, Antonios M. (Frontiers in Pharmacology, 2019)
Background: Apathy is one of the most prevalent neuropsychiatric symptoms encountered in Alzheimer disease (AD) and may be an early sign in the development of dementia persisting over the disease course. It has been associated with poor disease outcome, impaired daily functioning, and significant caregiver distress. Early diagnosis and timely treatment of apathy in AD are of great importance. However, approved agents for apathy are still missing. Methods: Within this context, we conducted an extensive electronic search in the databases included in the National Library of Medicine, PsychInfo and Google Scholar for studies that have investigated the effect of pharmacological treatments in apathy in AD. There were no limitations regarding study design and all care settings were considered for inclusion. Structured measures for level of evidence and study quality were employed to evaluate the results. Results: A total of 1607 records were identified, 1483 records remained after the removal of duplicates and were screened; 166 full-text articles were selected and assessed for eligibility and a remaining ninety unique studies and relevant reviews were included in the qualitative synthesis. Acetylcholinesterase inhibitors, gingko biloba, methylphenidate, were found to be successful in reducing apathy in patients with AD. Methodological heterogeneity in the studies and the small amount of studies where apathy was the primary outcome are limiting factors to assess for group effects. Conclusions: Pharmacological treatment of apathy in AD is an underexplored field. Standardized and systematic efforts are needed to establish a possible treatment benefit. Elucidating the pathophysiology of apathy and its components or subtypes will inform disease models and mechanistic drug studies that can quantify a benefit from specific agents for specific AD groups.